The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1038/sj.bjc.6603207
|View full text |Cite
|
Sign up to set email alerts
|

Established breast cancer risk factors by clinically important tumour characteristics

Abstract: Breast cancer is a morphologically and clinically heterogeneous disease; however, it is less clear how risk factors relate to tumour features. We evaluated risk factors by tumour characteristics (histopathologic type, grade, size, and nodal status) in a populationbased case -control of 2386 breast cancers and 2502 controls in Poland. Use of a novel extension of the polytomous logistic regression permitted simultaneous modelling of multiple tumour characteristics. Late age at first full-term birth was associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
145
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(160 citation statements)
references
References 38 publications
12
145
2
1
Order By: Relevance
“…particular, findings from three studies (Rosen et al, 1982;Stalsberg et al, 1989;Claus et al, 1993) could not be included in the metaanalysis because they were based on analyses conducted only within breast cancer cases, and findings on age at first birth from another study (LiVoisi et al, 1982) could not be incorporated because they were based on a different reference group. None of the five previous studies (Li et al, 2003(Li et al, , 2006(Li et al, , 2007Garcia-Closas et al, 2006;Rosenberg et al, 2006) for which comparable estimates of the effect of age at menarche were available, reported a significant difference in the effect of age at menarche on lobular compared with ductal cancer, although one study did find a significantly greater effect of age at menarche on lobular compared with ductal cancer, specifically among postmenopausal women (Li et al, 2008). The overall relative risk in women whose age at menarche was 14 or more, compared to less than 12, was 0.95 (0.92 -0.99) for ductal cancer and 0.77 (0.71 -0.83) for lobular cancer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…particular, findings from three studies (Rosen et al, 1982;Stalsberg et al, 1989;Claus et al, 1993) could not be included in the metaanalysis because they were based on analyses conducted only within breast cancer cases, and findings on age at first birth from another study (LiVoisi et al, 1982) could not be incorporated because they were based on a different reference group. None of the five previous studies (Li et al, 2003(Li et al, , 2006(Li et al, , 2007Garcia-Closas et al, 2006;Rosenberg et al, 2006) for which comparable estimates of the effect of age at menarche were available, reported a significant difference in the effect of age at menarche on lobular compared with ductal cancer, although one study did find a significantly greater effect of age at menarche on lobular compared with ductal cancer, specifically among postmenopausal women (Li et al, 2008). The overall relative risk in women whose age at menarche was 14 or more, compared to less than 12, was 0.95 (0.92 -0.99) for ductal cancer and 0.77 (0.71 -0.83) for lobular cancer.…”
Section: Resultsmentioning
confidence: 99%
“…For most of the reproductive factors considered, the relative risks for mixed ductal lobular cancer were intermediate between those found for ductal and lobular cancer. Several studies (LiVoisi et al, 1982;Rosen et al, 1982;Ewertz and Duffy, 1988;Stalsberg et al, 1989;Claus et al, 1993;Wohlfahrt et al, 1999;Li et al, 2003Li et al, , 2006Li et al, , 2007Li et al, , 2008Garcia-Closas et al, 2006;Rosenberg et al, 2006;Granstrom et al, 2008) have published findings on the relationship between reproductive factors and specific histological types of breast cancer and, although the majority found no significant differences in the effects of reproductive risk factors according to histological type, most lacked statistical power. Indeed only three studies (Stalsberg et al, 1989;Wohlfahrt et al, 1999;Li et al, 2008) have reported significant differences according to histological type for at least one aspect of reproductive history; two (Stalsberg et al, 1989;Wohlfahrt et al, 1999) found that increasing age at first birth was associated with a significantly greater relative risk of lobular cancer and/or tubular cancer than of ductal cancer, and one (Li et al, 2008) found a significantly greater effect of age at menarche on lobular compared with ductal breast cancer among postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…Among the studies that have, the association between combination hormone replacement therapy and risk of invasive breast cancer differed for ductal and lobular cancers in most studies, 5-10 but not all. 11 These findings suggest that the effects of other exogenous hormonal treatments, such as oral contraceptives, may also differ by histologic type.It has been consistently shown that oral contraceptive use is associated with an increased risk of breast cancer in young women, 12-25 but not older women. 21,[23][24][25] Recently, Newcomer et al 26 reported that current oral contraceptive use, recent use, and older age at first use are associated with an increased risk of invasive lobular breast cancer, but not invasive ductal breast cancer in a population of middleaged women, suggesting that oral contraceptives may have effects related to specific histologic subtypes.…”
mentioning
confidence: 84%
“…Among the studies that have, the association between combination hormone replacement therapy and risk of invasive breast cancer differed for ductal and lobular cancers in most studies, [5][6][7][8][9][10] but not all. 11 These findings suggest that the effects of other exogenous hormonal treatments, such as oral contraceptives, may also differ by histologic type.…”
mentioning
confidence: 84%
“…The design of this population-based breast cancer case -control study has been described (Garcia-Closas et al, 2006a). Eligible cases included women aged 20 -74 years who were Polish residents of either Warsaw or Łódź with pathologically or cytologically confirmed in situ or invasive breast cancer, newly diagnosed in 2000 -2003.…”
Section: Study Populationmentioning
confidence: 99%